2001
DOI: 10.1038/sj.leu.2402053
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical and molecular remission after allogeneic stem cell transplantation (SCT) in patients with poor prognosis non-Hodgkin's lymphoma

Abstract: From 1987 to 1999 35 patients with poor prognosis non-Hodgkin's lymphoma (NHL) underwent allogeneic stem cell transplantation (SCT) at the University Hospitals of Vienna and Graz. Initial biopsy specimens were reclassified according to the Revised European-American Classification of Lymphoid Neoplasms (REAL). All patients surviving 28 days engrafted. Twenty-eight of them (93%) attained clinical remission. At the last follow-up 14 patients were alive and disease-free at a median of 5.0 (range, 2.3-12.9) years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…29,30 Although there are no available randomized data to show superiority of an allogeneic approach in NHL, the advantage of tumor-free stem cells and a graft-versus-lymphoma effect make this an attractive alternative for young patients with a history of heavy pretreatment or refractory lymphoma. 3,14,31,32 A graft-versus-lymphoma effect may overcome chemotherapy resistance and allow long-term survival in a minority of refractory lymphoma patients. 33 Unfortunately , improvements in relapse-free survival after allogeneic SCT are generally offset by increased treatment-related mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Although there are no available randomized data to show superiority of an allogeneic approach in NHL, the advantage of tumor-free stem cells and a graft-versus-lymphoma effect make this an attractive alternative for young patients with a history of heavy pretreatment or refractory lymphoma. 3,14,31,32 A graft-versus-lymphoma effect may overcome chemotherapy resistance and allow long-term survival in a minority of refractory lymphoma patients. 33 Unfortunately , improvements in relapse-free survival after allogeneic SCT are generally offset by increased treatment-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…15,33,44 This indicates that CBV is sufficiently immunosuppressive to allow engraftment of donor hematopoietic cells. Other investigators have shown that CBV permits allogeneic stem cell engraftment in lymphoma patients with prior doselimiting radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Relapse is also not consistently decreased in the presence of GVHD 19,[20][21][22][23][24][25] (Table 2) nor increased after transplantation with T-cell-depleted marrow. [26][27][28] Isolated but impressive cases of response to withdrawal of immunosuppression and to donor leukocyte infusions have also been reported in some, 19,29,30 but not most cases.…”
Section: Why Consider Allosct?mentioning
confidence: 99%
“…[19][20][21][22][23][24][25]27,38,44,45 Those refractory to salvage chemotherapy at the time of transplant generally have eventfree survival less than 25%, and in some cases no event-free survival 20,22 because of both increased rates of relapse and increased transplant-related mortality. This pattern is not dissimilar to that seen with autoSCT, suggesting that there is only a limited role for alloSCT to overcome chemoresistance.…”
Section: Importance Of Chemosensitivitymentioning
confidence: 99%
“…9,10 Monitoring MRD is an essential tool for risk group stratification and appears to be useful for predicting relapse in some hematopoietic and lymphoid malignancies of humans. 10,[11][12][13] In addition, several reports document the usefulness of MRD to provide a molecular assessment of treatment efficacy for diffuse large B-cell lymphoma (DLBCL) in humans, [14][15][16] which is the disease to which high-grade B-cell lymphoma in dogs has been compared. We previously reported a highly sensitive MRD detection system in canine lymphoma by a real-time PCR that enabled detection of 1 tumor cell per 10 4 peripheral blood mononuclear cells (PBMCs).…”
mentioning
confidence: 99%